Radiotherapy quality assurance in the TROG 12.01 randomised trial and its impact on loco-regional failure - Corry, June; Moore, Alisha; Kenny, Liz; Wratten, Chris; Fua, Tsien; Lin, Charles; Porceddu, Sandro; Liu, Chen; Ruemelin, Michael; Sharkey, Amy; McDowell, Lachlan; Wilkinson, Dean; et al. (Frontiers in Oncology, 2024)
Introduction There is no consensus as to what specifically constitutes head and neck cancer radiotherapy quality assurance (HNC RT QA). The aims of this study are to (1) describe the RT QA processes used in the TROG 12.01 study, (2) review the RT QA processes undertaken for all patients with loco-regional failure (LRF), and (3) provide prospective data to propose a consensus statement regarding the minimal components and optimal timing of HNC RT QA. Materials and methods All patients undergoing RT QA in the original TROG 12.01 study were included in this substudy. All participating sites completed IMRT credentialling and a clinical benchmark case. Real-time (pre-treatment) RT QA was performed for the first patient of each treating radiation oncologist, and for one in five of subsequent patients. Protocol violations were deemed major if they related to contour and/or dose of gross tumour volume (GTV), high dose planning target volume (PTVhd), or critical organs of risk (spinal cord, mandible, and brachial plexus). Results Thirty HNROs from 15 institutions accrued 182 patients. There were 28 clinical benchmark cases, 27 pre-treatment RT QA cases, and 38 post-treatment cases. Comprehensive RT QA was performed in 65/182 (36%) treated patients. Major protocol violations were found in 5/28 benchmark cases, 5/27 pre-treatment cases, and 6/38 post-treatment cases. An independent review of all nine LRF cases showed major protocol violations in four of nine cases. Conclusion Only pre-treatment RT QA can improve patient outcomes. The minimal components of RT QA in HNC are GTVs, PTVhd, and critical organs at risk. What constitutes major dosimetric violations needs to be harmonised.